2017
DOI: 10.5114/fn.2017.68579
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates intermittent hypoxia induced up-regulation of proinflammatory cytokines in microglia through inhibiting the activation of NF-Bκ/p38 MAPK signalling

Abstract: A b s t r a c t As immune sentinels of the central nervous system (CNS), microglia is pivotal cellular mediator of neuroinflammatory processes. Activation of microglia might elicit the expression of proinflammatory cytokines involved in the progression of neuroinflammatory diseases. Numerous studies have demonstrated that propofol (2,6-diisopropylphenol) has an effective anti-inflammatory property. Intermittent hypoxia (IH), as a result of obstructive sleep apnoea (OSA), could lead to neuron damage and neuroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Liu et al. suggested that propofol attenuated intermittent hypoxia induced upregulation of proinflammatory cytokines in microglia through inhibiting the activation of NF‐κB/p38 MAPK signaling. Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. suggested that propofol attenuated intermittent hypoxia induced upregulation of proinflammatory cytokines in microglia through inhibiting the activation of NF‐κB/p38 MAPK signaling. Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK and NF-κB signaling pathways are confirmed to play crucial roles in inflammatory response (Chen et al 2018, Gao et al 2018. Suppressing the abnormal activation of MAPK and NF-κB pathways has been reported to attenuate IH-induced inflammation (Kang et al 2017, Liu et al 2017. Moreover, MAPK activation has also participated in IH-induced apoptosis (Wu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental evidence suggests that many chronic inflammations can cause tumours, and the interaction between immune cells can stimulate tumour cell proliferation and angiogenesis (Amara & Tiriveedhi, ). Macrophages, neutrophils and other inflammatory cells often produce reactive oxygen species, resulting in protein and tissue damage and permanent DNA damage, and inflammatory processes also affect tumour progression (Liu, Sun, Ren, Chen, & Xu, ). There were three kinds of NOS isomers in the human cells, and the neuronal NOS (nNOS) and endothelial NOS (eNOS) constitutively expressed in the cells and produced NO at the nanomole level in the Ca 2+ ‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%